A Guidebook for Riverside Regeneration Artery - Transforming Riversides for the Future - Bothmann, Frank; Kerndlmaier, Rudolf; Koffeman, Albert I.; Mandel, Klaus; Wallbank, Sarah (Springer Berlin Heidelberg : Imprint: Springer, 2006)
"Artery" is an initiative on a European scale, funded by the INTERREG IIIB NWE programme, which puts riverside restoration and regeneration at the heart of regional strategies, helping communities across Europe 'turn back to face the water'. In this book the implemented strategies will be discussed, including public-private-partnership, public participation, awareness programs and regional development strategies. The book functions as a guide to facilitate similar future projects in other regions. The valuable experience and methods of trans-national cooperation should be made available to other developers, regional planners, project managers and politicians.